1998
DOI: 10.1016/s0370-2693(98)00083-5
|View full text |Cite
|
Sign up to set email alerts
|

Low-mass e+e− pair production in 158 A GeV Pb-Au collisions at the CERN SPS, its dependence on multiplicity and transverse momentum

Abstract: We report a measurement of low-mass electron pairs observed in 158 GeV/nucleon Pb-Au collisions. The pair yield integrated over the range of invariant masses 0.2 ≤ m ≤ 2.0 GeV/c 2 is enhanced by a factor of 3.5 ± 0.4 (stat) ± 0.9 (syst) over the expectation from neutral meson decays. As observed previously in S-Au collisions, the enhancement is most pronounced in the invariant-mass region 300-700 MeV/c 2 . For Pb-Au we find evidence for a strong increase of the enhancement with centrality. In addition, we show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
38
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(44 citation statements)
references
References 22 publications
(25 reference statements)
6
38
0
Order By: Relevance
“…We emphasize as well that the behavior of the curves in Fig. 3, which correspond to a finite system, has a similar tendency to the CERES data [1,2]. For comparison, we present in Fig.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…We emphasize as well that the behavior of the curves in Fig. 3, which correspond to a finite system, has a similar tendency to the CERES data [1,2]. For comparison, we present in Fig.…”
supporting
confidence: 65%
“…That is why, the dileptons (e + e − and µ + µ − pairs) observed in high-energy heavy ion collisions secure an excellent opportunity for obtaining information on the initial state and the evolution of the system created in a collision. The enhancement with an invariant mass of 200 ÷ 800 MeV observed by the CERES collaboration [1,2] in the production of dileptons has received recently a considerable attention and has been studied in the framework of various theoretical models (for the review, see Ref.[3]). It was found that a large part of the observed enhancement is due to the medium effects (see Refs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dilepton spectroscopy allows to measure the in-medium properties without distortion due to final state interactions (FSI). The CERES collaboration at CERN, for example, measured the low-mass e + e − pair production in heavy-ion collisions and observed an enhancement in the mass range of 0.3 GeV/c 2 ≤ m e + e − ≤ 0.7 GeV/c 2 over the yield expected from the known sources in pp collisions [15,16]. More recently, analyzing π + π − pairs the STAR experiment at RHIC observed a decrease of the ρ meson in-medium mass in peripheral Au+Au collisions [17].…”
mentioning
confidence: 99%
“…Fig. 7 shows the dielectron invariant mass distributions measured by NA45 in different colliding systems [22][23][24]. While the more elementary collisions (pBe and p-Au) are reproduced within errors by final state Dalitz and direct decays of neutral mesons as…”
Section: The Pastmentioning
confidence: 99%